- #1

mimsy57

- 18

- 0

df/dx=.2

d^2f/dx^2=.6

df/dy=.4

d^2f/dy^2=.9

(you do not need to go beyond the second derivative for this problem)

2. I know from class how to do this if one variable changes. I thought I knew how to do it with 2, but I am getting the wrong answer.

if I wanted to do f(1.2,3) I would do f(1,3)+df/dx*(.2)+d2f/dx2*(.2)^2=7+(.2)*(.2)+(.2)^2/2*(.6).

so I thought if I wanted to do both, I would expand in both variables:

f(1.2,3.1) ~ f(1,3)+df/dx*(.2)+d2f/dx2*(.2)^2+df/dy*(.1)+d2f/dy2*(.1)^2

Why is this coming out to be the wrong answer?